Multiple resistive switching behaviours of CH 3 NH 3 PbI 3 perovskite film with different metal electrodes - How G.T.S.; Talik N.A.; Yap B.K.; Nakajima H.; Tunmee S.; Goh B.T. (Elsevier B.V., 2023)
Charge trapping; Electrodes; organic-inorganic materials; Perovskite; Silver; Switching; Filamentary conduction; Memory applications; Organic-inorganic; Organic-inorganic hybrid; Resistive Random Access Memory (ReRAM); Resistive switching; Resistive switching memory; Write-once-read-many; Random access storage